Un/Divided Loyalties in Anita Rau Badami’s Tamarind Mem - Palla Mária (PÁZMÁNY PAPERS, 2025)
This paper aims to explore the tension between mobility, migration, and travelling, on the one hand, and settlement, stability, housing, and accommodation on the other, as a major theme in the South Asian Canadian diasporic author Anita Rau Badami’s debut novel Tamarind Mem (1996). As seen, it is my contention that questions of loyalty and belonging arise from this tension, which manifests itself in the variously troubled relationships the two female protagonists have to their numerous homes, real or imaginary, during their migration inside or outside of India because for them, the home as such is always imbued with memories of the familial and communal past, as well as a sense of isolation and dislocation. The examination of questions of loyalty and belonging in relation to the home in such a context necessitates the use of diaspora criticism as well as the application of cognitive literary studies in the analysis to follow.